Progress in catalytic synthesis of advanced carbon nanofibers. Issue 27 (27th June 2017) - Lu, Wenyang; He, Ting; Xu, Bang; He, Xin; Adidharma, Hertanto; Radosz, Maciej; Gasem, Khaled; Fan, Maohong
Abstract : Carbon nanofibers (CNFs) have wide applications in various high-tech areas. Abstract : Carbon nanofibers (CNFs) have wide applications in various high-tech areas. The demand for CNFs can exponentially increase due to the rapid development of advanced functional materials. Accordingly, a transformational progress is being made in synthesizing CNFs, especially functionalized CNFs. A dominant CNF synthesis pathway is catalytic chemical vapor deposition (CCVD). Therefore, the goal of this work is to review the most recent progress in CCVD synthesis of functional CNFs and to understand how the process conditions and catalysts, especially metal catalysts, affect the physical and chemical properties of the produced CNFs.